New Zealand : Technical Assistance Report-Report on the Monetary and Financial Statistics Mission. (IMF Staff Country Reports; Country Report, 2019)
At the request of the Reserve Bank of New Zealand (RBNZ), and with the support of the IMF's Asia and Pacific Department (APD), a monetary and financial statistics (MFS) technical assistance (TA) mission visited Wellington, New Zealand during October 1-12, 2018.1 The mission's main objectives were to assist the RBNZ to: (i) complete the central bank Standardized Report Form (SRF 1SR); (ii) review the source data and bridge table used to produce Other Depository Corporations (ODCs) Standardized Report Form (SRF 2SR);(iii) assist the RBNZ to produce additional historical data in the SRFs 1SR and 2SR for the past five years; (iv) review the available source data for the compilation the Other Financial Corporations (OFCs) Standardized Report Form (SRF 4SR); (v) prepare metadata for the central bank, ODC, and OFC surveys; and (vi) agree on a timetable for RBNZ's SRF-reporting of its MFS.